Investigation of the Effect of Pasteurization on the Viability of Cryptosporidium parvum in Cow's Milk by Propidium Monoazide qPCR - Aydemir, Selahattin; Durmaz, Hisamettin; Aydemir, Mehmet Emin; Kilic Altun, Serap; Demir, Abdulbaki; Halidi, Ahmet Galip; Arslan, Ali (Ankara Microbiology Soc, 2023)
Cow's milk, which is one of today's most important food sources, can be a reservoir for many patho-gens that create a risk to public health. One of these pathogens is Cryptosporidium parvum. The oocysts of C.parvum, an obligate intracellular parasite, cause infection when ingested orally. The oocysts scattered around with the feces of infected cows or calves can contaminate raw milk and this is frequently seen in dairy farms. The aim of this study was to investigate the viability of C.parvum by propidium monoazide (PMA)-quantitative polymerase chain reaction (qPCR) method after heat treatment applied to contami- nated raw cow's milk. For the study, 50 ml of unpasteurized cow's milk was contaminated with 5 X 105 C.parvum oocysts and portioned into 1.5 ml microcentrifuge tubes. Three groups, namely the control group, pasteurization group and boiling group were formed. No warming procedure was applied to the control group. In the pasteurization group, the milks in microcentrifuge tubes were poured into the wells of the dry block heater set to 71.7 degrees C and incubated for five seconds. At the end of the period, the milks were transferred to the wells of the cold metal tube, which was removed at-20 degrees C with the help of a micropipette, and incubated for five seconds. The milks in the boiling group were incubated for two minutes in a dry block heater set to 95 degrees C. After the heat treatment, the milks in microcentrifuge tubes were transferred to 10 ml centrifuge tubes, PBS was added to make the final volume 10 ml, and centrifuged at 4000 rpm for 20 minutes. After this process was repeated twice, 400 mu l of PBS was added to the precipitate remaining at the bottom, and the precipitate was homogenized. One sample of each group was applied with PMA, while PMA was not applied to the other sample. PMA-applied samples were incubated for five minutes at room temperature and in the dark, and then exposed to UV light for five minutes in the device with cooling feature. The oocysts were collected by centrifugation at 5000 g for five minutes. After DNA isolation from oocysts, SYBR Green real time PCR (Rt-PCR) was performed using primers amplifying the COWP gene region. As a result of SYBR Green Rt-PCR, the mean Ct values of the control without PMA, pasteurization and boiling groups were determined as 25 +/- 1.24, 23 +/- 0.98 and 26 +/- 1.03, respectively. While no peak was obtained in the boiling group after PMA application, the mean Ct values of the control and pasteurization groups were 28 +/- 1.38 and 31 +/- 1.46, respectively. As a result, it was concluded that live C.parvum cysts in milk could be detected by PMA-qPCR method and live oocysts could be found in pasteurized milk.
Keywords: Pasteurization; PMA-qPCR; viability; milk